Effectiveness of Land and Building Tax Collection Management in Saritani Village - ilen dakio; ikram muhammad; karlina napu (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims 1) To determine the effectiveness of PBB collection management in Saritani Village and 2) To determine the determinants of the effectiveness of PBB collection management in Saritani Village. This research will be conducted using a descriptive qualitative approach. Data collection techniques used are observation, interviews and documentation. There were 2 people who became research informants. The data analysis technique used is data reduction, presentation and conclusion drawing. The results of the study indicate that (1) The effectiveness of land and building tax collection in Saritani Village is not maximized because the implementation of collection is still not optimal because tax officials are considered not able to maximize both from the planning, driving, organizing and monitoring aspects which have not been effective. (2) The determining factor in collecting Land and Building Tax in Saritani Village is because there is still a lack of support for facilities that support the implementation of Tax collection in Saritani Village because Saritani Village is very wide. Even the very manual land and building tax collection system makes collection effectiveness not work well. Then due to the lack of awareness of taxpayers in paying land and building taxes.